Structural Violence and Societies of Fear in Hamid’s “The Prisoner” and Tanweer’s “The Scatter Here is Too Great” (Journal of Asian Development Studies, 2025)
This paper aims to investigate the portrayal of different forms of structural violence that impact the constructs of social order and rhetoric around it in Karachi – one of the major metropolitan centers of Pakistan. Through a close textual analysis of Omar Shahid Hamid's “The Prisoner” and Bilal Tanweer's “The Scatter Here is Too Great”, our study examines the underlying economic factors that give rise to various manifestations of structural violence in Karachi. For this research, we primarily draw upon Johan Galtung's concept of "structural violence" to analyze the detailed portrayal of alienation, elitism, and social stratification within the selected novels. This study mainly focuses on the underlying causes of structural violence, the effect of unjust neoliberal policies, and the subsequent establishment of societies of fear in Karachi. Ultimately, our research calls for greater social awareness and reforms to foster more inclusive and equitable socio-cultural structures in the city for the establishment of a peaceful society.